The relevance of philosophy - Mackinnon, Edward (Cambridge Scholars Publishing, 2018)
As the culmination of a long career in philosophy plus long excursions in physics, history, and theology, the author reflects on what must be done to make philosophy relevant to non-philosophers. Philosophers, the author argues, should go beyond specialized philosophical studies, acquire a knowledge of other disciplines, and then try to clarify the way things hang together on a deep conceptual level. A novel feature of this book is that it emphasis on public morality, understanding it in an evolutionary perspective, and guides efforts to raise accepted moral standards.